Comparison between 1.5 and 3-Tesla MRI findings in Ménière’s disease - Duarte, Juliana Antoniolli; Garcia, Marcio Ricardo Taveira; Souza, Soraia Ale; Monsanto, Rafael da Costa; Sarpi, Maira de Oliveira; Juliano, Amy; Gananca, Fernando Freitas (Frontiers in Neurology, 2024)
Introduction: 3T-MRI of the inner ear has been used to identify the endolymphatic hydrops (EH) phenomenon, and less frequently 1.5T-MRI. The aim of this study was to assess whether there was agreement between findings of EH at 1.5T MRI and those obtained at 3.0T MRI in patients clinically diagnosed with definite Ménière Disease (MD). Methods: Crosssectional, blinded study was conducted in a tertiary neurotology ambulatory practice. Thirty patients with clinical diagnosis of unilateral definite MD was included. Two MRI exams (1.5T and 3.0T) were performed for each patient and were evaluated by 2 examiners (E1, E2) who were blinded to the symptomatic ear. An analysis of intra-and inter-examiner agreement was performed. It was determined whether there was an association between MRI findings and disease duration, symptom severity, and MD clinical stage. Results: E1 found EH at 3T-MRI in 26 (86.66%) patients and at 1.5T-MRI in 25 (83.33%). E2 found EH in 25 (83.33%) patients in 3T-MRI and in 22 (73.33%) at 1.5T-MRI. The agreement between the examiners' assessments in relation to the EH was high (0.844) for the 3T MRI and substantial for the 1.5T, both statistically significant. There was no statistically significant relationship between EH imaging findings and clinical disease severity and course. Discussion: 1.5T and 3.0T MRI images agreed regarding the findings of absence or presence of cochlear hydrops (CH) and vestibular hydrops (VH). The degrees of CH and VH found at 3.0T MRI in symptomatic ear were not associated with clinical aspects and the stage of disease.1 0 (0,0) 2 4 (13,3) 3 23 (76,7) 10 10 4 3 (10,0)